Somatosensory Evoked Potentials for prediction of outcome in Pediatric Cardiac Intensive Care Unit. Issue 1 (January 2019) - Pro, S.; Iodice, F.; Alessandri, B.; Di Chiara, L.; Di Capua, M.
Abstract : Somatosensory Evoked Potentials (SEPs) have been shown to provide prognostic information in both adults and children with acute brain injury. Aim of this study is to evaluate SEPs prospectively as a predictor of neurological outcome in children with ischemic brain injury. We performed SEPs in 29 consecutive patients with acute ischemic injury. SEPs were classified as bilaterally normal (SEPs-N/N), bilaterally absent (SEPs-A/A), unilaterally absent (SEPs-N/A). Ten pts have SEPs-N/N (outcome: 5 with normal outcome, 4 with epilepsy, 1 exitus); 3 pts have SEPs N/A (outcome: all with hemiparesis and one also with cognitive impairment); 15 pts with SEPs A/A (outcome: 9 exitus and 6 with tetraparesis and cognitive impairment). We suggest that SEPs may be a good predictor of neurological outcome in children with acute ischemic brain injury.